La riduzione del rischio nella movimentazione del paziente obeso / Risk reduction in handling obese patients - Capodaglio, E.M.; Capodaglio, P. (La Medicina del Lavoro, 2008)
L’obesità costituisce attualmente uno dei maggiori problemi sanitari, con una rapida crescita della prevalenza mondiale e in ogni fascia d’età. Frequentemente essa è associata con condizioni degenerative e disabilità, che spesso richiedono il ricovero ospedaliero. Gli operatori ospedalieri addetti alla movimentazione ed assistenza di pazienti obesi sono esposti a rischi rilevanti. Il livello di rischio può essere ridotto tramite la programmazione di interventi integrati, rivolti particolarmente a sviluppare una specifica competenza negli operatori, all’adozione di linee guida operative per la sicurezza, all’uso di ausili tecnologici. L’articolo presenta e commenta le linee guida presenti in letteratura per la gestione in sicurezza del paziente obeso ospedalizzato, insieme ad una rassegna degli ausili tecnologici adatti per la movimentazione ed assistenza dei pazienti obesi con dipendenza estensiva o parziale in ambito ospedaliero. Risk reduction in handling obese patients Background: Hospital staff are exposed to significant risk in the manual handling and care of obese patients. Objectives: to illustrate how risk reduction can be achieved by means of integrated measures, particularly aimed at developing specific know-how among the operators, and the use of safety guidelines and technical aids for transferring obese patients in various situations. Methods: on the basis of the recent literature, the present article reviews the technological aids and the preventive procedures that ensure safe transfer and health care of obese patients. Results: Many devices are available in the USA for the handling and assisting the obese patient; however, much remains to be done for the development of specific equipment. In Italy, along with knowledge of the devices, specific competence needs to be promoted among the operators dealing with obese patients. Organizational and structural issues arise from this new specialty. Conclusions: An integrated approach, requiring suitable environments, ergonomic devices, standard procedures and personnel competence needs to be adopted in order to reduce the risk in health-care workers dealing with obese patient.